(untitled) (International Journal of Engineering and Computer Science, 2018)
Cloud computing provides application and services over the Web. The services are provided to all over the world by the data centers, which is referred to as the "cloud." This mechanism provides solution to the many network connections and Computer systems in online services. This shows the broad reach of internet, while we are simplifying its complexity. Any user with an Internet connection can use the cloud services provided by it. when these services are connected, users can share information to each other and also to the web. But before entering into the cloud we have know that the rapid growth of cloud computing also increases sever security concern. The Security of cloud is a big issue for open system and cloud computing. It has many security issues like analyzing the data privacy, security auditing and data monitoring. Till now the existing models are too far away to cover the full complexity of the cloud computing model. Some papers has been proposed previously for security of cloud computing but the implementation proposed by them is not enough for full complexity of cloud. In this paper we are going to implement a new mathematical algorithm for low level of risk in Cloud computing environment. The purpose of this attempt is to focus (or provide mechanism) on some new points where the security level founds very low.